THE IMPLEMENTATION OF TOTAL PHYSICAL RESPONSE STORYTELLING (TPRS) METHOD IN TEACHING VOCABULARY TO YOUNG LEARNERS : A Descriptive Qualitative Study of Teacher's Techniques and Students' Responses in one Elementary School in Cianjur - Gantika, Ginta (2013)
The study entitled The Implementation of Total Physical Response Storytelling (TPRS) Method in Teaching Vocabulary to Young Learners is aimed at investigating how the English teacher applied TPRS method in teaching vocabulary to the 4th graders and figuring out the students' responses towards the implementation of the method. This study employed a descriptive qualitative study and was conducted in one of elementary schools in Cianjur. An English teacher and her 27 fourth grade students were the subjects of this study. To obtain the data, a classroom observation and interview with the English teacher were conducted. The findings revealed that the teacher applied four steps of TPRS method with two additional steps whichwere labeled as teacher's preparation steps. The first two (preparation) steps were choosing new vocabularies that would be introduced to the students and also the stories. The second step was showing the words, the third step was telling the words, the next step was storytelling, and the last step was vocabulary learning activity. The students responded physically as instructed. Moreover, they gave correct responses with full of enthusiasm to the teacher's instructions. Additionally, this method is able to motivate students to learn vocabulary, since the students' responses towards the teacher's instructions increase in each word and step. Another result was that TPRS can help students' attention last longer because the method employs stories and physical moves that children like. Key Words: TPRS method, Vocabulary, Young learners, Physical moves, Instructions Penelitian berjudul Penggunaan Metode Total Physical Response Storytelling (TPRS) dalam Mengajarkan Kosa Kata Bahasa Inggris untuk Anak Usia Dini ini bertujuan untuk meneliti bagaimana guru bahasa Inggris menggunakan metode TPRS ini dalam mengajarkan kosa kata bahasa Inggris kepada siswa kelas 4 SD dan mencari tahu bagaimana respon siswa terhadap penggunaan metode TPRS tersebut. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif dan dilakukan di salah satu sekolah dasar di Cianjur. Guru bahasa Inggris dan 27 orang siswanya menjadi subjek dari penelitian ini. Observasi kelas dan wawancara dengan guru bahasa Inggris dilakukan untuk memperoleh data. Berdasarkan hasil yang diperoleh dari penelitian ini, guru bahasa Inggris yang diteliti melakukan empat langkah dari metode TPRS ini dan dua langkah tambahan yang ia sebut sebagai langkah persiapan. Dua langkah pertama sebagai langkah persiapan adalah memilih kosa kata yang akan diperkenalkan kepada siswa dan juga memilih cerita. Langkah ke dua adalah showing the words, langkah ke tiga adalah telling the words, langkah selanjutnya adalah storytelling, dan langkah terakhir adalah vocabulary learning activity. Siswa merespon dengan gerakan seperti yang diinstruksikan. Siswa juga merespon perintah guru dengan benar dan baik juga dengan penuh antusias. Metode TPRS ini juga dapat memotivasi siswa untuk belajar kosa kata karena respon siswa terhadap perintah guru meningkat di setiap kata dan langkah. Hasil yang lain menunjukkan bahwa TPRS dapat membantu perhatian siswa menjadi lebih lama karena metode ini menggunakan cerita dan gerakan badan yang disukai anak-anak.